Segurança do paciente na gestão de prontuários - Aquino, Pablo Lincoln Sherlock de (2015)
The Patient Safety has been, in the last decades a thematic evidenced in the Brazilian and world scenario. There are cases that refer to bad prescription, errors in medication administration , stress and professional disillusion. Attached to concerns regarding the quality of medical records, Patient Safety becomes a study of high importance for Risk Reduction, both for patients as for professionals and health services. Therefore, this study concerned to better understand the reality of management of records of Alcides Carneiro University Hospital (ACUH) a federal public institution in the city of Campina Grande, Paraíba. The aspirations for improvements in service hospital records, along with initial actions of ACUH Management Risk and Patient Safety Center, were the main indicators for this study to have its start up. The focus of this work was to understand the situation seen as problematic by the institution Hospital Records Division and, through observations and systemic reviews, identify opportunities for improvement. The methodology used was the Soft Systems Methodology (SSM), recognized worldwide in the management of public health services, especially in studies carried out in National Health Service (NHS) in Britain. The application of SSM had allowed greater understanding of how the records management is conducted in ACUH, and the main obstacles for attendance to Brazilian national guidelines Risk Management and Patient Safety. In addition to organizational learning, this study led to the construction of a project named the Medical Records Management Improvement Program (MRMIP), which may be applied by the administration of ACUH.